Media Framing by Inilah.com of the Collapse of Pondok Pesantren Al-Khoziny on TikTok - Shofa Zahrani; Mustofa Hilmi; Kirana Nur Lyansari (Jurnal Dakwah dan Komunikasi, 2026)
Purpose − The aim of this study is to analyze the framing by Inilah.com on the incident as well as which issues are highlighted in its reporting.   Method –   This study employs a qualitative descriptive approach using primary and secondary data. Primary data consist of TikTok videos uploaded by Inilah.com related to the collapse of the Al-Khoziny Pondok Pesantren, published between September 29 and October 9, 2025. Data were collected through purposive sampling, focusing on content containing news elements such as chronology, causes, impacts, and responses. Secondary data were obtained from relevant literature and online sources. Data analysis applies Robert N. Entman’s framing model, examining problem definition, causal interpretation, moral evaluation, and treatment recommendation. The analysis focuses on video content, language, and visual elements to identify framing patterns and emphasized issues, supported by source triangulation.   Findings −   The results of the study show that Inilah.com frames the incident gradually, starting with an emphasis on humanitarian aspects and the emergency situation, then leading to the technical causes of the building, moral assessments regarding the importance of safety, and finally the issue of legal responsibility. This pattern shows a strategy of issue selection and emphasis on certain aspects to build emotional engagement with the audience before directing attention to structural issues. This study is limited to one account and one incident, so the findings cannot yet be generalized. Future research is recommended to broaden the study's objects to achieve a more comprehensive understanding of disaster framing..